Peranan Pendidikan Kewarganegaraan dalam Mengembangkan Karakter dan Perilaku Sosial Peserta Didik Kelas Rendah di UPTD SD Negeri 122332 Pematangsiantar T.A 2022/2023 - Lidya Tondang; Corry Corry; Tuangkus Harianja (Journal on Education, 2023)
This study aims to examine how the role of Civics subjects carried out by teachers is to build the character and social behavior of students. The research method used in this study was a qualitative research method with a descriptive approach, namely by conducting interviews with several teachers at the UPTD SD Negeri 122332 Pematangsiantar and filling out questionnaires related to social behavior which were distributed to 24 low-grade students. This research was conducted in November 2022. Based on the results of the research conducted, it can be concluded that Civics is actually a noble program because there are moral values ​​in shaping the character of students. Therefore, realizing the importance of the role of Civics in the process of cultivating and empowering students, then through Civics in schools it should be developed as a socio-cultural vehicle for building a democratic life. But in reality, so far Civic Education still has many weaknesses and shortcomings and aspects of social behavior in low-class students at UPTD SD Negeri 122332 Pematangsiantar in general, including helping behavior, cooperation, giving, sharing, honesty and considering the rights and welfare of others almost all were carried out and many were approved by low-grade students at UPTD SD Negeri 122332 Pematangsiantar. The presentation aspect of the social behavior of UPTD SD Negeri 122332 Pematangsiantar students reached the high category with a presentation of 48% with a total of 12 students out of 24 of the total number of students. It can be concluded that the number of students who have social behavior in the low class UPTD SD Negeri 122332 Pematangsiantar has shown a very good category.